IMPLEMENTACIÓN DEL LISTADO DE VERIFICACIÓN DE CIRUGÍA SEGURA - Arribalzaga, Eduardo B.; Lupica, Liliana; Delor, Stella Maris; Ferraina, Pedro A. (Revista Argentina de Cirugía, 2022)
Background: The checklist procedure is a useful tool within the strategies for safety of surgical interventions. Objective: Utility of the checklist for detection of technical or human failures. Place: Operating rooms Division of State University Hospital. Design: Observational prospective exploratory with retrospective analysis. Population: Consecutive scheduled operations during 12 months. Method: Indication loudly in different operative moments of a standards checklist for the responsible surgeon, the anesthesiologist and nurse circulating. Results: There were 3680 operations programmed with implementation of the checklist in 100 %. There were 2116 failures (57.5%): of them attributable to the human factor 98,12% and technicals only 0.18%. In the preoperative, the most common failure was the lack of informed consent; in the intraoperative, lack of foresight critical events and in the immediate postoperative period, lack of operative protocols and discrepancy in the counting of gauze. Conclusion: The incidence of error in surgery needs to be reduced by a guidelines provided by the checklist, rapid and simple procedure which requires the commitment of the surgical team acting.